2015
DOI: 10.17344/acsi.2015.1849
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Habit on the Dissolution of Simvastatin Single Crystals

Abstract: In order to achieve better in-vivo performance of the final dosage form comprising a poorly soluble drug the physicochemical properties of the active pharmaceutical ingredient can be altered not only by changing the solid state form but also through the conversion of their crystal habits. To elucidate this approach in the case of simvastatin, the dissolution behaviour of large crystals with the same internal structure but expressing different crystal habits was studied using atomic force microscope. The obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Therefore the effects of polymeric additives on the dissolution of FFA cocrystals are attributed to surface adsorption of the polymers through specific interactions with the crystal surface, in particular, hydrogen bonding. [17][18][19][20]23,26,38,39 Among the polymers used in this study, PEG, containing a high percentage of hydrogen acceptors in the backbone, is the most hydrophilic, while PVP-VA, containing 40% acetate side chains in comparison to PVP, is the most hydrophobic. 11 Based on the dissolution experiment of the single FFA I crystal, the FFA I (100) face is more hydrophobic because it has a slower face dissolution rate in Figure 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 COs were the only solid phase in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the effects of polymeric additives on the dissolution of FFA cocrystals are attributed to surface adsorption of the polymers through specific interactions with the crystal surface, in particular, hydrogen bonding. [17][18][19][20]23,26,38,39 Among the polymers used in this study, PEG, containing a high percentage of hydrogen acceptors in the backbone, is the most hydrophilic, while PVP-VA, containing 40% acetate side chains in comparison to PVP, is the most hydrophobic. 11 Based on the dissolution experiment of the single FFA I crystal, the FFA I (100) face is more hydrophobic because it has a slower face dissolution rate in Figure 5 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 COs were the only solid phase in Figure 9(b).…”
Section: Discussionmentioning
confidence: 99%
“…As a crystal dissolves, rates of dissolution of its faces are distinctly different due to their different interactions with the dissolution medium. A polar solvent is more likely to interact with polar crystal faces where polar atoms or functional groups are exposed normal to the faces . Through measurement of the physical retreat rates of individual faces of a single crystal, a crystal surface dependent dissolution rate can be obtained, which can be used to determine the relationship between crystal morphology and bulk dissolution rates. , This knowledge of anisotropic dissolution behavior of single crystals can highlight the factors affecting crystal dissolution, which is crucial in the design, evaluation and control of therapeutic efficacy of solid dosage forms. , …”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly applied methods in the crystal structure studies is powder X-ray diffraction (PXRD). PXRD delivers data on the unit cell parameters, and thus sometimes serves as an alternative route to a single crystal X-ray diffraction (SCXRD) when the latter is not attainable [ 36 ]. Further, in contrast to SCXRD, PXRD can be applied to study the mixture of solids and, in some cases, determine the quantitative phase composition [ 37 ].…”
Section: Methods Applied For Analysis Of Hydratesmentioning
confidence: 99%
“…It was observed that the dissolution concentration value of crystal samples was less if the crystal size distribution was in a wide range. It is essential to limit the crystal size distribution, increase the dissolution concentration, and provide reproducible properties of the final dosage form (Bukovec et al, 2015).…”
Section: Evaluation Of Dissolution Concentrationmentioning
confidence: 99%